2013
DOI: 10.1021/jo4018414
|View full text |Cite
|
Sign up to set email alerts
|

Direct Asymmetric α-Allylation of α-Branched Aldehydes by Two Catalytic Systems with an Achiral Pd Complex and a Chiral Primary α-Amino Acid

Abstract: Direct α-allylation of α-branched aldehydes was successfully carried out with a readily available allyl ester by combined use of two catalytic systems: Tsuji-Trost allylation reaction with an achiral palladium complex and enamine catalysis with a chiral primary α-amino acid. A quaternary carbon stereogenic center was constructed stereoselectively to give various 2,2-disubstituted pent-4-enals in good yields with high enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 58 publications
(19 reference statements)
0
20
0
Order By: Relevance
“…However, noticeably absent is the use of protected α‐amino‐ and α‐hydroxy‐ acetaldehydes 5. There are merely four reactions reported to date, which involve Pd‐catalyzed allylation to afford γ,δ‐unsaturated adducts in racemic form5a,b or at best 46 % ee 5c. The use of a suitably protected α‐aminoacetaldehyde in a dual catalytic process of the type shown in Scheme could result in a fully stereodivergent synthesis of β,β′‐disubstituted α‐amino acid derivatives.…”
Section: Methodsmentioning
confidence: 99%
“…However, noticeably absent is the use of protected α‐amino‐ and α‐hydroxy‐ acetaldehydes 5. There are merely four reactions reported to date, which involve Pd‐catalyzed allylation to afford γ,δ‐unsaturated adducts in racemic form5a,b or at best 46 % ee 5c. The use of a suitably protected α‐aminoacetaldehyde in a dual catalytic process of the type shown in Scheme could result in a fully stereodivergent synthesis of β,β′‐disubstituted α‐amino acid derivatives.…”
Section: Methodsmentioning
confidence: 99%
“…123 A related allylation of α,α -disubstituted aldehydes was developed by Yoshida, which involves capture of the π-allylpalladium intermediate by an enamine derived from a chiral α-stereogenic amino acid. 124, 125 Most recently, Stoltz and Marek reported decarboxylative Tsuji-Trost allylations of fully-substituted amide enolates to form acyclic quaternary carbon stereocenters. 126 Remote electronic effects of the phosphine ligand XXXVII were required to enforce optimal levels of enantioselectivity.…”
Section: Acyclic Quaternary Carbon Stereocentersmentioning
confidence: 99%
“…Soon after, Yoshida and co-workers reported a similar reaction catalyzed by chiral amino acids and palladium. 12 Finally, Zhang et al reported the α-allylation of branched aldehydes by using pyrrolidine and chiral palladium(II) complexes. 13 In both examples, the branched aldehydes were obtained in good yields and with excellent enantioselectivities, albeit in low diastereoselectivities in Zhang's case.…”
Section: Scheme 5 Enantioselective Version Of the Allylation Of Lineamentioning
confidence: 99%